Influence of mulching, liming and farm yard manures on production potential, economics and quality of maize (Zea mays L.) under rainfed condition of Eastern Himalaya - Kumar, Rakesh (Bangladesh Journal of Botany, 2018)
A field experiment was conducted to study the effect of mulching, liming and farm yard manures on productivity and quality of maize on a sandy loam soil at Agricultural Research Farm of ICAR RC NEH Region Nagaland Centre, Jharnapani, Medziphema during two consecutive rabi seasons of 2010-12 under the rainfed conditions of Eastern Himalaya. Treatment comprised of two mulches (without mulch and straw mulch) in main plot, four levels of lime (control, 0.2, 0.4 and 0.6 t/ha) in sub plot and three levels of farm yard manures (4, 8 and 12 t/ha) in sub-sub plot and replicated thrice in split-split plot design. The significant improvement in yield attributes (cob length, number of rows/cob, number of grain/row, number of grain/cob and 1000-grain weight), yields (grain, stover and biological), economics (gross, net returns and benefit: cost ratio) and quality attributes (carbohydrate, starch and sugar) of maize were recorded in straw mulched plot over no mulch in both the years. The straw mulching recorded 15.9 and 16.5% increase in grain yield and 20.4 and 22.2% in stover yield over no mulch. Application of 0.6 t lime/ha in furrow recorded the significantly higher yield attributes, grain yield (3.85 and 3.97 t/ha), stover yield (4.16 and 4.33 t/ha), gross return (41.87 and 43.25 ×103/ha), net return (28.45 and 29.83 ×103/ha) and benefit: cost ratio (1.55 and 1.63) and quality attributes over rest of the levels, respectively. Application of farm yard manures @ 12 t/ha noted significantly higher yield attributes yield and quality attributes of maize over rest of the treatments. Similar effect of these treatments was observed on gross return of Rs. 40.75 and 41.78 × 103/ ha, net return of Rs. 27.5 and Rs. 28.53 × 103/ha and benefit : cost ratio of 1.52 and 1.57 in both the years, respectively.